1999
DOI: 10.1002/(sici)1521-3935(19990601)200:6<1245::aid-macp1245>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Functionality and stereochemical design of silicon-containing polymers

Abstract: SUMMARY: Molecular design and precision synthesis of silicon-containing polymers are described. The low rotational barrier energy around the silicon-oxygen bond was taken advantage of in designing a selectively oxygen permeable membrane material and new side-chain liquid crystalline polymers. The low surface free energy of polysiloxane graft copolymers was utilized in surface modification of a film consisting of a blend. Syntheses of stereoregular and/or optically active silicon-containing polymers from optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…These observations indicate that in the studied nanocomposite membranes the mobility of the polyether segments surrounding the nanoparticles having dimethylsilyl spacer is higher compared to the nanocomposites where the nanoparticles do not have such moiety. It is well known that the polymers containing flexible Si-O linkage in the main and side chains exhibit high gas permeability which stems from the low energy barrier of rotation of the Si-O linkage of the dimethylsilyl group [34]. In the PEG grafted nanoparticles obtained from glycidyl POSS (Scheme 1a) and glycidyldimethlysilyl POSS (Scheme 1b) the ligands are connected to the silsesquioxane core through Si-C and Si-O bonds, respectively.…”
Section: Influence Of Structural Features Of the Nanofillers Upon Gasmentioning
confidence: 99%
“…These observations indicate that in the studied nanocomposite membranes the mobility of the polyether segments surrounding the nanoparticles having dimethylsilyl spacer is higher compared to the nanocomposites where the nanoparticles do not have such moiety. It is well known that the polymers containing flexible Si-O linkage in the main and side chains exhibit high gas permeability which stems from the low energy barrier of rotation of the Si-O linkage of the dimethylsilyl group [34]. In the PEG grafted nanoparticles obtained from glycidyl POSS (Scheme 1a) and glycidyldimethlysilyl POSS (Scheme 1b) the ligands are connected to the silsesquioxane core through Si-C and Si-O bonds, respectively.…”
Section: Influence Of Structural Features Of the Nanofillers Upon Gasmentioning
confidence: 99%
“…The side chain with both flexible Si-O linkages and bulk SiMe 3 groups, which are moving in the material, may control the diffusibility of the permeating gas. Similar gas permeation behaviors have been reported previously for oligosiloxane-substituted polymers such as polystyrene, 19,20 polyimide, 21,22 and polyacetylene.…”
Section: Gas Permeation Properties Of Poly(norbornene) With Siloxane mentioning
confidence: 99%
“…It is known that the appearance of flexible Si–O bonds not only in the backbone chains but also in the side groups results in significant decrease in the glass transition temperature and increase in permeability, though reduction of permselectivity. Thus, it has been shown that some polystyrenes having oligodimethylsiloxanyl substituents in the para-position of phenylene group has T g as low as about 260 K (that is, are rubbery) and are characterized by permeability much higher than that of polystyrene and substantially reduced permselectivity. Since no significant reduction of T g and separation factors are observed for ROMP poly( III ) and addition-type poly( III ) (Tables and ), it is likely that the main factors that determine the transport parameters of the two novel polymers are the big size and the presence of siloxy fragments in the introduced Si-containing side groups. Hence, it is worthwhile to continue studies of the effects of Si–O containing side groups on the properties of norbornene polymers of both types.…”
mentioning
confidence: 99%